Monocyte TREM-1 Levels Associate With Anti-TNF Responsiveness in IBD Through Autophagy and Fcγ-Receptor Signaling Pathways - Prins, Marileen M.; Verstockt, Bram; Ferrante, Marc; Vermeire, Séverine; Wildenberg, Manon E.; Koelink, Pim J. (Frontiers in Immunology, 2021)
The expression of Triggering Receptor Expressed on Myeloid cells (TREM)-1 has been described as a predictive marker for anti-Tumor Necrosis Factor (TNF)-α monoclonal antibody (mAb) therapy responsiveness in patients with inflammatory bowel disease (IBD). Here we investigated expression of TREM-1 specifically in CD14+ monocytes in relation to anti-TNF response. The pretreatment TREM-1 expression levels of CD14+ monocytes of Crohn’s disease (CD) patients were predictive of outcome to anti-TNF mAb therapy, with low TREM-1 expression associated with response to anti-TNF. FACSorting of CD14+ monocytes with different TREM-1 levels showed that differentiation towards regulatory CD206+ M2 type macrophages by anti-TNF was suppressed in CD14+ monocytes with high TREM-1 expression. Activity of the Fcγ-Receptor and autophagy pathway, both necessary for M2 type differentiation and the response to anti-TNF, were decreased in CD14+ monocytes with high expression of TREM-1. We confirmed that the activity of the Fcγ-Receptor pathway was decreased in the CD patients that did not respond to anti-TNF therapy and that it was negatively correlated with TREM-1 expression levels in the CD patient cohort. In conclusion, our results indicate that TREM-1 expression levels in CD14+ monocytes associate with decreased autophagy and FcγR activity resulting in decreased differentiation to M2 type regulatory macrophages upon anti-TNF mAb treatment, which may explain anti-TNF non-response in IBD patients with high expression levels of TREM-1.